Pengaruh Abdominal Stretching Exercise Terhadap Keluhan Low Back Pain (LBP) Pada Pekerja Tenun di Desa Troso - Melania Putri Devitasari; Prita Adisty Handayani; Siti Juwariyah; Swanny Trikajanti Widyaatmadja (JURNAL KEPERAWATAN SUAKA INSAN (JKSI), 2026)
Weavers are often restricted from maintaining ergonomic postures due to static work activities and repetitive movements that can cause complaints of low back pain. The purpose of this study is to evaluate the effect of abdominal stretching exercise on reducing low back pain complaints. A quasi-experimental design (one-group pre-posttest) was used in this study with 45 weavers as a research sample, taken by total sampling technique. The Wilcoxon test results indicated a p-value of <0.001, demonstrating a statistically significant decrease in low back pain complaints. After the intervention, the majority of respondents experienced a decrease in pain levels from moderate to mild. This study demonstrates the potential of abdominal stretching exercise as a non-pharmacological approach to managing low back pain in weaving workers; however, additional studies with more robust methodologies are required to substantiate these results.